2022
DOI: 10.1053/j.semnuclmed.2021.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Nuclear Medicine in Europe

Abstract: The COVID-19 pandemic has profoundly changed hospital activities, including nuclear medicine (NM) practice. This review aimed to determine and describe the impact of COVID-19 on NM in Europe and critically discuss actions and strategies applied to face the pandemic. A literature search for relevant articles was performed on PubMed, covering COVID-19 studies published up until January 21, 2021. The findings were summarized according to general and specific activities within the NM departments. The pandemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It has globally affected health care services, medical education and research activities including the field of nuclear medicine (NM). The particular impact of pandemic in NM departments has been recently documented by several international surveys [1][2][3][4][5] reporting an overall decline in diagnostic and therapeutic activities. These studies reported a reduction in the number of NM procedures performed resulting in disruption of usual education activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has globally affected health care services, medical education and research activities including the field of nuclear medicine (NM). The particular impact of pandemic in NM departments has been recently documented by several international surveys [1][2][3][4][5] reporting an overall decline in diagnostic and therapeutic activities. These studies reported a reduction in the number of NM procedures performed resulting in disruption of usual education activities.…”
Section: Introductionmentioning
confidence: 99%